Proceedings of the Thirtieth International Joint Conference on Artificial Intelligence 2021
DOI: 10.24963/ijcai.2021/162
|View full text |Cite
|
Sign up to set email alerts
|

Weakly-Supervised Spatio-Temporal Anomaly Detection in Surveillance Video

Abstract: In this paper, we introduce a novel task, referred to as Weakly-Supervised Spatio-Temporal Anomaly Detection (WSSTAD) in surveillance video. Specifically, given an untrimmed video, WSSTAD aims to localize a spatio-temporal tube (i.e., a sequence of bounding boxes at consecutive times) that encloses the abnormal event, with only coarse video-level annotations as supervision during training. To address this challenging task, we propose a dual-branch network which takes as input the proposals with multi-granulari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Sultani et al [22] propose the MIL framework using only video-level labels and introduce the large-scale anomaly detection dataset, UCF-Crime. This work inspires quite a few follow-up studies [28], [17], [4], [14], [26], [25], [6], [23], [26]. .…”
Section: General Anomaly Detectionmentioning
confidence: 80%
“…Sultani et al [22] propose the MIL framework using only video-level labels and introduce the large-scale anomaly detection dataset, UCF-Crime. This work inspires quite a few follow-up studies [28], [17], [4], [14], [26], [25], [6], [23], [26]. .…”
Section: General Anomaly Detectionmentioning
confidence: 80%
“…Waqas et al [41] applied pretrained 3D networks to extract spatiotemporal features and trained the classifier with multi-instance learning techniques. Following this work, Zhu and Newsam [45] introduced optical flow; Lin et al [53] proposed a dual-branch network; Lv et al [54] replaced the feature extractor with a TSN and proposed an HCE module to capture dynamic changes; Feng et al [55] applied pseudolabel and self-attentive feature encoders for training; Wu et al [56] also proposed a dual-branch network but with tubular and temporal branches and so on.…”
Section: Segment-level Methodsmentioning
confidence: 99%
“…Another method for handling anomaly detection and classification using a weakly supervised learning model was provided by Majhi et al [16]. Employing multi-detail ideas in both the temporal and spatial dimensions as input, a dual branch network has been developed by Wu et al [17]. To detect video anomalies, Cao et al [18] suggested taking into consideration the spatial-temporal relationships between video parts.…”
Section: Introductionmentioning
confidence: 99%